PSIX-9 Tick-borne disease is associated with altered ingestive behaviors and reduced feed and water intake by weaned dairy calves. (7th December 2018) - Silper, B F; Oliveira Júnior, B; Ribas, M; Machado, F; Lima, J; Cavalcanti, L; Coelho, S
Abstract: Tick-borne disease (TBD), a hemolytic disease complex of challenging timely diagnosis, causes extensive losses to tropical-region dairy-replacement rearing systems. Objectives were to investigate the association between TBD and intake and ingestive behaviors. Weaned calves (n = 35; groups of 12, 12, and 11) enrolled at 108 ± 8 days old were group-housed for 4 weeks in a pen containing 12 electronic feed bins and 2 electronic water bins. Data were automatically collected via radio-frequency identification ear-tags at each bin visit and summarized within bin type (feed or water) as intake (kg/day), frequency (visits/day) and duration (minutes/day) of visits. Water and TMR were provided ad libitum. Tick-borne disease was confirmed if hematocrit was ≤ 25% at weekly clinical exams. The 12 calves with positive diagnoses received antimicrobial and antipyretic treatment. Day of diagnosis was set as day 0 and sick period as days -4 to +4. A within-calf healthy-period mean (HP) was calculated using all days between consecutive negative diagnoses for each response variable. Each sick day was compared with within-calf HP using repeated-measures models. Feed intake was lesser than during HP on days -1, 0, and +1, and frequency and duration of feed bin visits were reduced between days -3 and +4 (P<0.05). Frequency of feed bin visits was reduced by 25% on day -3 (58.0 ± 7.2 vs. 77.4 ± 7.6 visits/day at HP; P<0.05). Water intake was reduced on day 0 (9.3 ± 1.3 kg/day vs. 13.2 ± 1.4 kg/day at HP; P<0.05). Water intake, frequency and duration of water bin visits were reduced on day +1 (P<0.05). These changes are in agreement with sickness behaviors and could be applied towards automated TBD detection. Timely treatment may reduce the convalescence period and improve prognosis, performance, and welfare. Precision technologies should be assessed for development of TBD detection algorithms.